Comparative Analysis of Copeptin, IL-6, and TNF-α as Predictive Biomarkers for Clinical Outcome in Moderate to Severe COVID-19 Patients - Harsini Harsini; Jatu Aphridasari; Sihsusetyaningtyas Tiominar Siregar (Jurnal Respirologi Indonesia, 2026)
Background: Cytokine release syndrome (CRS) plays a central role in disease progression, driven by pro-inflammatory cytokines such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), as well as neuroendocrine stress markers such as copeptin. Perbandingan langsung biomarker copeptin, IL-6, dan TNF-α sangat penting untuk mengidentifikasi prediktor hasil COVID-19 yang paling andal, terutama pada kasus sedang hingga berat. This retrospective clinical study aimed to evaluate the correlation of copeptin, IL-6, and TNF-α levels with the clinical outcomes of patients with moderate to severe COVID-19. Methods: The study included patients who met the selection criteria and provided written informed consent. A sample size of 41 was determined via power analysis to achieve 80% power at a 0.05 significance level. Consecutive sampling was employed to select participants. The study utilized medical records of patients with moderate to severe COVID-19 who underwent copeptin, IL-6, and TNF-α testing. Correlation analyses and Bonferroni corrections were performed using SPSS® ver. 21. Results: Results revealed a moderate positive correlation between copeptin levels and patient outcomes (Bonferroni correlation=0.597; P<0.001). A weak positive correlation was observed between IL-6 levels and outcomes (Bonferroni correlation=0.239; P=0.055), while a negligible positive correlation was found for TNF-α levels (Bonferroni correlation=0.140; P=0.177), which was not statistically significant. Conclusion: Copeptin emerged as a more sensitive biomarker for predicting the outcomes of COVID-19 patients. Elevated copeptin levels were associated with a poorer prognosis. Furthermore, its stability in serum renders copeptin a more sensitive biomarker than IL-6 and TNF-α.